A Face to Meet the Faces : An Anthology of Contemporary Persona Poetry - De la Paz, Oliver, 1972-; Brown, Stacey Lynn (Book collections on Project MUSE., 2012)
"The literary tradition of persona, of writing poems in voices or from perspectives other than the poet's own, is ancient in origin and contemporary in practice. The embodiment of different voices is a moment of true empathy, as the author moves beyond his or her own margins to fully inhabit the character, personality, and mindset of another human being. While there are a great number of poems written in persona, there are no current anthologies that collect and celebrate the diverse writers who work in this mode today. Stacey Lynn Brown and Oliver de la Paz have selected a superb collection of approximately two hundred persona poems. These poems embody characters from popular culture, history, the Bible, literature, mythology, and their diversity is reflective of the wide range of authors working in this genre. The anthology also contains brief explanatory notes written by the poets to help historicize and contextualize their characters and personae"--